KONSEP HIJAU: PENERAPAN GREEN CONSTITUTION DAN GREEN LEGISLATION DALAM RANGKA ECO-DEMOCRACY - Nurmardiansyah, Eko (Veritas et Justitia, 2015)
Abstract Green principle is to be understood as a commitment to the environment. It is part of a broader ideology that places human relationship with the natural world at the center. Green is a process, not a status, a verb, not an adjective. Â Good environmental awareness become an important and urget global discourse. Eco-crasy should become the guiding principle informing Indonesianâ state policy making (political law) in environmental protection and management.Â  However, the concept of Eco-crasy should be further spelled out into a green constitution, green legislations and green budgeting.